Network pharmacology-based screening of the active ingredients and potential targets of the genus of Pithecellobium marthae (Britton & Killip) Niezgoda & Nevl for application to Alzheimer's disease. Issue 16 (18th August 2019) - Zhang, Han; Yan, Zhi-Yang; Wang, Yu-Xi; Bai, Ming; Wang, Xiao-Bo; Huang, Xiao-Xiao; Song, Shao-Jiang
Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder associated with synaptic dysfunction, pathological accumulation of β -amyloid (A β ), and neuronal loss. Given the prevalence of AD and the lack of effective long-term therapies, there is a pressing need to discover viable leads that can be developed into clinically approved drugs with disease-modifying effects. The analysis of current reported literatures confirms the importance of the plants of Pithecellobium genus as candidate against AD. Hence, it is necessary to identify selective anti-dementia agents from this genus. To explore potential compounds with marked effect on AD in Pithecellobium genus, a compound database based on the methods of network pharmacology prediction was established in this paper by constructing the compound-disease target network. The result showed that the most effective compound in the plants of this genus might be (7′ R, 8′ R )-7′-methoxyl strebluslignanol, and the most potential target might be Macrophage colony-stimulating factor 1 receptor. Abstract :